2012
DOI: 10.1016/j.ecoenv.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genotoxicity of quinolone and fluoroquinolones contaminated soil with the Vicia faba micronucleus test

Abstract: , et al.. Assessment of the genotoxicity of quinolone and fluoroquinolones contaminated soil with the Vicia faba micronucleus test. Ecotoxicology and Environmental Safety, Elsevier, 2012, 76, pp.187-192. <10.1016/j.ecoenv.2011 a b s t r a c tThe genotoxicity of quinolone and fluroquinolones was assessed using the micronucleus (MN) test on Vicia faba roots by direct contact exposure to a solid matrix. Plants were exposed to quinolones (nalidixic acid) and fluoroquinolones (ciprofloxacin and enrofloxacin) alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…For example, they may cause DNA damage, adduct formation, DNA hypermethylation in kidney cells of Carassius auratus , and synchronous teratogenic effects on Cyprinus carpio [8][9]. To date, most previous research has focused on the toxicity and relative mechanist effects for single DKA compound [7][9]; few studies have addressed exposure to mixtures of DKA compounds. In real-world environments, the joint action of different pollutants may be very complex.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they may cause DNA damage, adduct formation, DNA hypermethylation in kidney cells of Carassius auratus , and synchronous teratogenic effects on Cyprinus carpio [8][9]. To date, most previous research has focused on the toxicity and relative mechanist effects for single DKA compound [7][9]; few studies have addressed exposure to mixtures of DKA compounds. In real-world environments, the joint action of different pollutants may be very complex.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines facilitate a resultant fatty liver by affecting the gene expression associated with lipid metabolism for increasing triglyceride (TG) and cholesterol biosynthesis and decreasing β-oxidation of fatty acids (Yin et al, 2006). Previous studies showed that DKAs have strong genetic toxicity resulting in DNA damage, adduct formation, DNA hypermethylation of kidney cells in Carassius auratus and teratogenic effects on Cyprinus carpio (Khadra et al, 2012;Li et al, 2010). Among the toxicities of quinolones, one major risk is their chondrotoxicity potential in juvenile animals, such as rats, dogs, rabbits, nonhuman primates, and others (Sheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports mainly focused on toxicity and associated mechanisms for a single DKA compound (Khadra et al, 2012;Li et al, 2010;Wang et al, 2014). However, little information is available on the aquatic toxicity of mixed DKAs using zebrafish (Danio rerio) as a model organism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that raw sludge contains some compounds that are toxic and genotoxic for plants. Among them, organic acids, phenolic and pharmaceuticals compounds such as antibiotic (El Hajjouji et al, 2007;Khadra et al, 2012;El Fels et al, 2014a). These results underline the efficiency of cocomposting process to degrade and stabilise these compounds, and especially the Cr(VI).…”
Section: Genotoxicity Assay Of Co-composting Aqueous Extract and Cr(vmentioning
confidence: 73%